2021
DOI: 10.52041/serj.v19i2.111
|View full text |Cite
|
Sign up to set email alerts
|

Paint-by-Number or Picasso? A Grounded Theory Phenomenographical Study of Students’ Conceptions of Statistics

Abstract: Statistics students’ conceptions of the work of statisticians and the discipline of statistics may play an important role in the topics to which they attend and their interest in pursuing further study. To learn about students’ conceptions, we collected open-ended survey responses from 44 undergraduate students who had completed introductory statistics courses. We used a grounded theory phenomenographical qualitative approach to identify several themes in students’ conceptions. In addition to the test-and-proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…In this paper, I use the term statistical perspective to represent broadly the views and conceptions one may have about statistics. These perspectives include some examination of one's disciplinary conception and epistemology for statistics (Diamond & Stylianides, 2017;Justice et al, 2020), as well as views about what it means to engage in statistical work (Wild & Pfannkuch, 1999;Wild et al, 2018). To better understand the perspectives of the GTAs in this study, I first provide some frame of reference by discussing expert perspectives on statistics.…”
Section: Framing Statistical Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper, I use the term statistical perspective to represent broadly the views and conceptions one may have about statistics. These perspectives include some examination of one's disciplinary conception and epistemology for statistics (Diamond & Stylianides, 2017;Justice et al, 2020), as well as views about what it means to engage in statistical work (Wild & Pfannkuch, 1999;Wild et al, 2018). To better understand the perspectives of the GTAs in this study, I first provide some frame of reference by discussing expert perspectives on statistics.…”
Section: Framing Statistical Perspectivesmentioning
confidence: 99%
“…To understand the nature of statistics, it is important to also unpack the nature of mathematics. Statistics draws much from mathematics, and naïve views of the two disciplines may simply note that statistics is mathematics or a branch of applied mathematics (Diamond & Stylianides, 2017;Justice et al, 2020), but such descriptions discredit the true nature of both mathematics and statistics (Cobb & Moore, 1997;Skemp, 1976;Wild et al, 2018).…”
Section: Perspectives On the Nature Of Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, many studies have identified the need for a relevant statistics education curriculum that can help students develop the type of statistical thinking needed to cope with the demands of the real world (Bansilal, 2014;Carver et al, 2016;Gattuso & Ottavani, 2011;Justice et al, 2020;North et al, 2014;Wessels & Niewoudt, 2013). Like most countries, the study of statistics forms part of the mainstream mathematics curriculum in schools and has traditionally been an under-represented strand in the core mathematics curriculum in South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Future research will use follow-up interviews to examine the trajectories of students' changing perspectives, participation, disciplinary identities, and interests.The American Statistical Association's (ASA) Guidelines for Undergraduate Statistics Programs highlights several important practices for the next generation of statistics students, including increased experience in data science and computing, working with complex data, using diverse models and analytical approaches, and communicating insights and methods to diverse audiences (ASA, 2014). As students enter undergraduate university programs with varied experiences and perspectives on the nature of statistical work (e.g., Gordon, 2004;Justice et al 2020), we see two reasons why it is important to understand student perspectives about the discipline. First, research conducted from constructivist theories of learning suggests that students learn best when they connect new content with their own experiences and conceptual frameworks (e.g., Bransford et al, 2000).…”
mentioning
confidence: 99%